Pro Apache Beehive - Kanchanavally, Srinivas. (Apress : Imprint: Apress, 2005)
If you want exposure to the new open source lightweight SOA-driven Apache Beehive framework project, then pick up Pro Apache Beehive, the first book on this MVC Web framework, which is increasingly gaining interest in the Eclipse community through Eclipse Pollinate. Author Kunal Mittal addresses specific Beehive topics such as page flows, controls, JSR 181 web services, XMLBeans and more. This book proceeds to describe how these technologies are used in WebLogic Workshop, and how other IDEs are extending support for these technologies. Mittal also compares PageFlows in Workshop to the Standard.